PROSES HEGEMONI SOSIAL DALAM NOVEL TANAH TABU KARYA ANINDITA S. THYAF (Social Hegemony Process in Anindita S. Thayf’s Tanah Tabu) - Kurniawati, Diyan (Balai Bahasa Sumatra Barat, 2016)
This research investigates social hegemony in Anindita S. Thyaf’s Tanah Tabu. This novel reveals social class changes among people in Baliem Valley, Papua since gold mining corporation started operating at this area. Using Gramsci’s theory of hegemony and feminism, this paper analyze the process of social hegemony around people in Baliem Valley. The step ofanalysis started by examined carefully the corporation’s method to get people sympathy for the corporation’s existence. Furthermore, analyzing continuous to social cultural changes asthe impact of hegemony superiority of corporation. Analyzing shows that the process of hegemony done by recognition new things, caring of children and doctrination about the importance of corporation for people. Even education doctrine toward women also strictly was given. As the result of these perfect method to hegemony people in Baliem Valley, the corporation successfully subordinate them. Hegemony successfully changes the life style of people in Baliem Valley.